Sudden death of an immunocompetent young adult caused by novel (swine origin) influenza A/H1N1-associated myocarditis - Gdynia, Georg; Schnitzler, Paul; Brunner, Eva; Kandolf, Reinhard; Bläker, Hendrik; Daum, Edith; Schnabel, Philipp Albert; Schirmacher, Peter; Roth, Wilfried (Virchows Archiv, 2011)
The main cause of death from novel (swine origin) influenza A/H1N1 infection is acute respiratory distress syndrome. Most fatal cases are immunocompromised patients or patients with a severe underlying disease. Here, we report a fatal case of acute interstitial myocarditis associated with novel influenza A/H1N1 infection in an immunocompetent young woman. A previously healthy 18-year-old woman experienced malaise, diarrhea, and fever for several days prior to a sudden collapse at home. Autopsy revealed a predominantly lymphocytic myocarditis in the absence of a significant respiratory tract infection. Infection with novel (swine origin) influenza A/H1N1 was confirmed by PCR analysis of blood as well as myocardial tissue. Influenza-caused diarrhea with consecutive hypokalemia potentially contributed to the fatal outcome of the myocarditis, characterized by ventricular fibrillation. In conclusion, sudden death by myocarditis may be a rare complication of novel influenza A/H1N1 infection in otherwise healthy individuals, even in the absence of significant respiratory tract infection.